Lithium-sulfur battery positive electrode material containing CNT-ZnO / Co catalyst, preparation method and application

By using CNT-ZnO/Co catalyst in the positive electrode material of lithium sulfur battery, the problem of low utilization of active sites of metal compound catalysts is solved, and higher battery performance and specific energy density are achieved.

CN119905590APending Publication Date: 2025-04-29XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510021253.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Among the existing lithium-sulfur battery positive electrode materials, the active site utilization rate of metal compound catalysts is low, resulting in limited catalytic effect, and the inactive material increases the weight and cost of the battery, affecting the specific energy density.

Method used

CNT-ZnO/Co catalyst was used to synthesize CNT-ZnCo by hydrothermal method, and then calcined at high temperature under a reducing mixed atmosphere to prepare a CNT-ZnO/Co catalyst supported by cobalt single atoms and zinc oxide, combining the conductivity of carbon nanotubes and the polarity of metal oxides to improve the conversion kinetics of polysulfides.

Benefits of technology

The discharge capacity, rate performance and cycling performance of lithium-sulfur batteries are improved, the utilization rate of catalytic active sites is maximized, the weight and cost of the battery are reduced, and the specific energy density is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905590A_ABST
    Figure CN119905590A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst as well as a preparation method and application of the lithium-sulfur battery positive electrode material. The preparation method comprises the following steps: firstly, synthesizing a zinc-cobalt layered double hydroxide (CNT-ZnCo) loaded on a carbon nano tube; and calcining at high temperature to obtain a catalyst containing cobalt monatomic and zinc oxide (ZnO) coexisting, and recording the catalyst as CNT-ZnO / Co. And mixing the obtained CNT-ZnO / Co and elemental sulfur, and heating by adopting a melt diffusion method to obtain the positive electrode material of the lithium-sulfur battery. According to the method, more active sites can be exposed in a reactant environment, the atom utilization rate is maximized, the conversion reaction kinetics of polysulfide can be improved, and the shuttle effect is relieved; the prepared positive electrode material can significantly improve the discharge capacity, rate capability and cycle performance of the lithium-sulfur battery; the preparation method is mild in reaction condition, convenient to operate and high in raw material utilization rate, so that the dosage is reduced, the raw material cost can be greatly reduced, and the preparation method is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur battery catalysis, and in particular relates to a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst, a preparation method and an application thereof. Background Art

[0002] The development of new energy has driven progress in the field of energy storage and increased society's demand for energy storage systems. At present, the development of commercial lithium-ion batteries is limited by the positive and negative electrode materials, and the energy density has approached its theoretical limit, making it difficult to meet people's future demand for energy storage. Therefore, it is necessary to develop new energy storage systems to support the development of green energy technology. Lithium-sulfur (Li-S) batteries have high energy density (2600Whkg –1 ), low cost, environmental friendliness and abundant sulfur resources have attracted more and more attention. However, lithium-sulfur batteries still face some problems. The inherent insulating properties of the active substance sulfur and the discharge product lithium sulfide lead to low conductivity of the positive electrode material, affecting the electrochemical reaction rate; the different densities of sulfur and lithium sulfide lead to volume expansion of the positive electrode material during charging and discharging, which will cause the pole piece to fall off; the intermediate product polysulfide generated during the redox process will dissolve in the electrolyte, resulting in a shuttle effect, causing irreversible loss of active substances, and seriously affecting battery performance; the slow reaction kinetics of polysulfides also limit the battery capacity;

[0003] In view of the above problems, developing and designing multifunctional composite positive electrode materials is one of the current ways to solve the above problems. At present, in order to improve the conductivity of lithium-sulfur (Li-S) battery positive electrode materials, carbon materials are usually used as sulfur carriers. Carbon materials have a large specific surface area and can provide more sulfur loading sites to improve the utilization rate of active sulfur. However, non-polar carbon materials have a weak effect on polysulfides and cannot effectively adsorb and catalyze the conversion of polysulfides. Therefore, the prior art has studied the use of polar metal compounds as catalysts in the design of lithium-sulfur battery positive electrode materials, such as metal nitrides, metal oxides, metal sulfides, etc. Metal compounds, etc. as catalysts can anchor polysulfides through strong polar-polar chemical interactions and accelerate the conversion of lithium polysulfides.

[0004] For example, the Xin Wang team at Jilin University introduced carbon nanofibers with MnS sulfate-philic sites as flexible interlayers into Li-S batteries, promoting synergy through physical inhibition, chemical adsorption, and conversion, thereby reducing the shuttle effect and accelerating the reaction kinetics. However, a careful study of the catalyst showed that most of the introduced metal sulfides were inactive in this reaction, adding unnecessary weight. Moreover, the adsorption and conversion process of LiPS occurs on the catalyst surface, and even relatively small catalyst particles have the characteristics of moderate metal utilization, which unnecessarily increases the weight and cost of the battery, thereby reducing its specific energy density.

[0005] Therefore, it is of great significance to develop catalytic materials with high atomic utilization and strong catalytic activity for application in lithium-sulfur batteries. Summary of the invention

[0006] The present invention provides a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst, a preparation method and an application thereof, so as to solve the problems in the prior art that the active sites of metal compounds used as catalysts cannot be fully utilized, the catalytic effect is limited, and the inactive materials affect the specific surface area and conductivity of the battery.

[0007] In order to achieve the above object, the present invention proposes the following technical solutions:

[0008] The first aspect of the present invention provides a method for preparing a positive electrode material for a lithium-sulfur battery containing a CNT-ZnO / Co catalyst, comprising the following steps:

[0009] Step 1, adding CNT to deionized water, stirring evenly to obtain a solution, taking cobalt salt, zinc salt and urea and adding them to the solution, hydrothermally synthesizing, washing, centrifuging and drying to obtain CNT-ZnCo powder;

[0010] Step 2: calcining CNT-ZnCo powder at high temperature in a mixed atmosphere to obtain a CNT-ZnO / Co catalyst;

[0011] Step 3: After mixing the obtained CNT-ZnO / Co catalyst and elemental sulfur, grind them evenly and transfer them to a reaction kettle, heat and keep them warm, and cool them to room temperature to obtain a lithium-sulfur battery composite positive electrode material.

[0012] Furthermore, in the above step 1, the amount of CNT used is 60-120 mg, the cobalt salt is 1 mmol, and the zinc salt is 0.2-4 mmol.

[0013] Furthermore, in the above step 1, the temperature of the hydrothermal synthesis is 90°C to 120°C, and the insulation time is 8 to 12 hours; the drying temperature is 40 to 60°C, and the time is 10 to 12 hours.

[0014] Furthermore, in the above step three, the mass ratio of CNT-ZnO / Co to elemental sulfur is 4:4-8.

[0015] Furthermore, in the above step 2, the high temperature calcination temperature is 400-700° C. and the time is 2-6 hours.

[0016] Furthermore, in the above step three, the heating temperature is 150-160° C., and the insulation time is 10-12 hours.

[0017] Furthermore, in the above step 2, the calcination atmosphere is a mixed atmosphere of argon and hydrogen or a mixed atmosphere of argon and ammonia.

[0018] Furthermore, the above-mentioned cobalt salt and zinc salt are nitrates or chlorides.

[0019] The second aspect of the present invention provides a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst obtained by the above preparation method.

[0020] The third aspect of the present invention provides an application of a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst in a lithium-sulfur battery, wherein the battery is assembled in sequence by at least a positive electrode sheet, an electrolyte, a separator, and a negative electrode metal lithium sheet, and the positive electrode sheet is made of a positive electrode material containing a CNT-ZnCo catalyst.

[0021] Compared with the prior art, the present invention has the following beneficial technical effects:

[0022] 1. The present invention first provides a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst. CNT-ZnCo is prepared by a hydrothermal method, and then prepared by a high-temperature calcination method in a reducing mixed atmosphere to obtain a derivative CNT-ZnO / Co loaded with cobalt single atoms and zinc oxide nanoparticles on carbon nanotubes as a catalyst. The obtained catalyst contains both metal oxides and metal single atoms, and the two coexist. On the one hand, the excellent conductivity and rich structure of carbon materials are used to improve the electrochemical performance of the battery. On the other hand, the metal oxide can also use its own unique polarity to accelerate the conversion of polysulfides and promote the deposition of lithium sulfide. There are a large number of highly catalytically active sites in metal single atoms. The present invention can expose more active sites to the reactant environment. Maximizing the atomic utilization rate can improve the conversion reaction kinetics of polysulfides and alleviate the shuttle effect.

[0023] 2. The catalyst CNT-ZnO / Co prepared by the present invention combines metal oxides and metal single atoms and loads them on a carbon base material to work together. Therefore, it has good conductivity and a large specific surface area. As a catalyst for preparing positive electrode materials, the prepared positive electrode materials can effectively improve the ion transfer rate and sulfur utilization rate. The presence of single atoms and metal oxides can increase the catalytic active sites in the composite material and enhance the adsorption capacity of polysulfides, thereby improving the conversion kinetics of polysulfides during electrochemical reactions, alleviating the shuttle effect of polysulfides, and reducing battery polarization. In chemical reactions, catalysts that exhibit high activity and conversion efficiency can effectively improve cycle life and capacity retention. Experimental results show that when CNT-ZnO / Co is applied to the positive electrode carrier of lithium-sulfur batteries, it can significantly improve the discharge capacity, rate performance and cycle performance of lithium-sulfur batteries.

[0024] 3. The preparation method of the present invention has mild reaction conditions and is easy to operate. At the same time, the raw material utilization rate of the present invention is high, so the amount used is reduced, which can greatly reduce the cost of raw materials and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The high-resolution TEM image and high-angle transmission scattering (HAADF-STEM) image and the corresponding EDS elemental spectrum provided in Example 1 of the present invention;

[0026] Figure 2 The adsorption-desorption isotherm curve and pore size distribution diagram provided in Example 1 of the present invention;

[0027] Figure 3 The XRD diagram provided by Example 1 of the present invention;

[0028] Figure 4 The battery assembled from Example 1 of the present invention and Comparative Example 1 is 0.1 mV S -1 CV curves under scanning rate;

[0029] Figure 5 The first cycle charge and discharge specific capacity diagram of the battery assembled in Example 1 of the present invention and Comparative Example 1 at a current density of 0.1C;

[0030] Figure 6 The cycle performance diagram of the battery assembled in Example 1 of the present invention and Comparative Example 1 at a current density of 1C;

[0031] Figure 7 This is a performance comparison diagram of the batteries assembled in Example 1 of the present invention and Comparative Example 1 at different rates;

[0032] Figure 8CV graph of a symmetrical battery in which the electrolyte of Example 1 of the present invention and Comparative Example 1 is 0.2M Li2S6 solution and a blank electrolyte. DETAILED DESCRIPTION

[0033] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific examples and drawings. The following examples are based on the technology of the present invention and provide detailed implementation methods and operating steps, but the protection scope of the present invention is not limited to the following examples.

[0034] The design idea provided by the present invention is: firstly, a zinc-cobalt layered double hydroxide (CNT-ZnCo) supported on a carbon nanotube is synthesized; a catalyst containing a cobalt single atom and zinc oxide (ZnO) is obtained by high-temperature calcination, which is recorded as CNT-ZnO / Co. The obtained CNT-ZnO / Co is mixed with elemental sulfur, and heated by a melt diffusion method to obtain a positive electrode material for a lithium-sulfur battery.

[0035] Example 1: A method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst, comprising the following steps:

[0036] Step 1, weigh 60 mg of CNT and add it to 60 ml of deionized water, stir and disperse it evenly by ultrasonic to obtain solution 1, weigh 1 mmol of Zn(NO)3·6H2O, 1 mmol of Co(NO)3·6H2O and 8 mmol of urea and add them to solution 1, stir and mix evenly by ultrasonic to obtain solution 1, put them into a reactor, perform hydrothermal synthesis, keep the temperature at 120°C for 12 hours, wash the obtained precipitate by centrifugation three times with deionized water and ethanol, and dry it in a vacuum oven at 60°C for 12 hours to obtain CNT-ZnCo powder;

[0037] Step 2: Weigh 200 mg of CNT-ZnCo, put it into a quartz tube of a tube furnace, and calcine it in a mixed atmosphere of 90% argon and 10% hydrogen at a temperature of 450° C. for 2 h to obtain a CNT-ZnO / Co catalyst;

[0038] Step 3: Preparation of positive electrode materials for lithium-sulfur batteries

[0039] The CNT-ZnO / Co catalyst obtained in step 2 and sulfur element are fully ground and mixed in a mass ratio of 4:6, sealed in a reaction kettle, heated to 155°C for melt sulfurization treatment, and kept warm for 12 hours to obtain a lithium-sulfur battery positive electrode material containing CNT-ZnO / Co catalyst.

[0040] Embodiment 2:

[0041] Step 1, weigh 60 mg of CNT and add it to 60 ml of deionized water, stir and disperse it evenly by ultrasonic, and obtain solution 1. Weigh 2 mmol of Zn(NO)3·6H2O, 1 mmol of Co(NO)3·6H2O and 8 mmol of urea and add them to solution 1. Stir and mix evenly by ultrasonic, and then put them into a reactor, keep it at 120°C for 12 hours, wash the obtained precipitate by centrifugation three times with deionized water and ethanol, and dry it in a vacuum oven at 60°C for 12 hours to obtain CNT-ZnCo-2 powder;

[0042] Step 2: Weigh 200 mg of CNT-ZnCo-2, put it into a quartz tube of a tube furnace, and calcine it in a mixed atmosphere of 90% argon and 10% hydrogen at a temperature of 450° C. for 2 h to obtain a CNT-ZnO / Co-2 catalyst;

[0043] Step 3: Preparation of positive electrode materials for lithium-sulfur batteries:

[0044] The CNT-ZnO / Co-2 catalyst obtained in step 2 and sulfur element are fully ground and mixed in a mass ratio of 4:6, sealed in a reaction kettle, heated to 155°C for melt sulfurization treatment, and kept warm for 12 hours to obtain a lithium-sulfur battery positive electrode material containing the CNT-ZnO / Co-2 catalyst.

[0045] Embodiment 3:

[0046] Step 1, weigh 60 mg of CNT and add it to 60 ml of deionized water, stir and disperse it evenly by ultrasonic, and obtain solution 1. Weigh 1 mmol of Zn(NO)3·6H2O, 2 mmol of Co(NO)3·6H2O and 8 mmol of urea and add them to solution 1. Stir and put them into a reactor after ultrasonic stirring, and keep them at 120°C for 12 hours. Wash the obtained precipitate by centrifugation three times with deionized water and ethanol, and dry it in a vacuum oven at 60°C for 12 hours to obtain CNT-ZnCo-3 powder.

[0047] Step 2: Weigh 200 mg of CNT-ZnCo-3, put it into a quartz tube of a tube furnace, and calcine it in a mixed atmosphere of 90% argon and 10% hydrogen at a temperature of 450° C. for 2 h to obtain a CNT-ZnO / Co-3 catalyst;

[0048] Step 3: Preparation of positive electrode materials for lithium-sulfur batteries:

[0049] The CNT-ZnO / Co-3 catalyst obtained in step 2 and sulfur element are fully ground and mixed in a mass ratio of 4:6, sealed in a reaction kettle, heated to 155°C for melt sulfurization treatment, and kept warm for 12 hours to obtain a lithium-sulfur battery positive electrode material containing CNT-ZnO / Co-3 catalyst.

[0050] Among the above embodiments, Embodiment 1 is the best embodiment.

[0051] See also Figure 1 , the high-resolution TEM image and high-angle transmission scattering (HAADF-STEM) image and corresponding EDS elemental map of the CNT-ZnO / Co catalyst provided in Example 1. Combining the TEM image and the EDS elemental map, it can be seen that the single-atom metal cobalt particles and zinc oxide supported on the carbon nanotubes, the single-atom metal and the metal oxide provide more active sites, further improving the catalytic activity of the material for polysulfide conversion;

[0052] See also Figure 2 , the adsorption-desorption isotherm and pore size distribution of the CNT-ZnO / Co catalyst provided in Example 1 of the present invention. It can be seen from the figure that the pores in the prepared material are mainly mesopores (2-50nm), with a specific surface area of ​​89.2m 2 g -1 , has a rich pore structure, which is conducive to the adsorption of polysulfides and the rapid transmission of ions.

[0053] See also Figure 3 , XRD pattern of the CNT-ZnO / Co catalyst provided in this Example 1. The peaks appearing in the XRD pattern correspond to ZnO and Co, which preliminarily proves that the cobalt single atom and zinc oxide supported on the CNT are successfully synthesized.

[0054] Comparative Example 1:

[0055] Step 1, weigh 60 mg of CNT and add it to 60 ml of deionized water, stir and disperse it evenly by ultrasonic to obtain solution 1, weigh 1 mmol of Zn(NO)3·6H2O, 1 mmol of Co(NO)3·6H2O and 8 mmol of urea and add them to solution 1, stir and mix evenly by ultrasonic to obtain solution 1, put them into a reactor, perform hydrothermal synthesis, keep the temperature at 120°C for 12 hours, wash the obtained precipitate by centrifugation three times with deionized water and ethanol, and dry it in a vacuum oven at 60°C for 12 hours to obtain CNT-ZnCo powder;

[0056] Step 2: Weigh 200 mg of CNT-ZnCo, put it into a quartz tube of a tube furnace, and calcine it in an argon atmosphere at a temperature of 450° C. for 2 h to obtain a CNT-ZnO / CoO catalyst;

[0057] Step 2: Preparation of positive electrode materials for lithium-sulfur batteries:

[0058] The CNT-ZnO / CoO catalyst obtained in step 2 and sulfur element are fully ground and mixed in a mass ratio of 4:6, sealed in a reaction kettle, heated to 155°C for melt sulfurization treatment, and kept warm for 12 hours to obtain a lithium-sulfur battery positive electrode material containing the CNT-ZnO / CoO catalyst.

[0059] The lithium-sulfur battery positive electrode materials provided in Example 1 and Comparative Example 1 were mixed with conductive carbon black and binder PVDF in a mass ratio of 8:1:1, and dispersant NMP was added. The mixed slurry was stirred to obtain a mixed slurry. The mixed slurry was coated on the surface of an aluminum foil with a coating thickness of 20 μm. The mixed slurry was vacuum dried at 60° C. for 12 h to obtain a positive electrode sheet.

[0060] Two types of lithium-sulfur batteries were assembled in sequence by assembling the positive electrode sheet, electrolyte, separator, and negative electrode metal lithium sheet. The test results are as follows:

[0061] See also Figure 4 The batteries assembled in Example 1 and Comparative Example 1 were 0.1 mV S -1 CV curves at scan rates. As can be seen from the figure, the CNT-ZnO / Co catalyst prepared in Example 1 has a faster current response and a higher current peak, indicating that it has a better catalytic ability for the conversion of polysulfides.

[0062] See also Figure 5 , the first cycle charge and discharge specific capacity of the battery assembled in Example 1 and Comparative Example 1 at a current density of 0.1C. It can be seen from the figure that there are two discharge platforms at about 2.3 / 2.1V and a charging platform at about 2.25V, which is consistent with the reaction mechanism of Li-S battery. And the initial discharge specific capacity of Example 1 is 1196.6mAh g -1 The initial discharge capacity is significantly higher than that of comparative example 1, which is 998.5 mAh g -1 ,The chemical interaction between CNT-ZnO / Co and polysulfides greatly improves the discharge specific capacity.

[0063] See also Figure 6 , the long cycle performance diagram of the battery assembled in Example 1 and Comparative Example 1 at 1C current density, showing an initial capacity of 725.3 mAh g -1 After 500 cycles at 1C current density, the capacity remains at 400.5 mAh g -1 , the calculated capacity decay rate per cycle is 0.0065%, indicating its good long-cycle stability;

[0064] See also Figure 7 , the performance comparison diagram of the battery assembled in Example 1 and Comparative Example 1 at different rates. After being tested under different current density conditions, the current density still has 780.4 mAh g when it returns to 0.1C. -1 The discharge specific capacity has good cycle reversibility and excellent rate performance;

[0065] See also Figure 8The symmetric battery of Example 1 and Comparative Example 1, in which the electrolyte is 0.2M Li2S6 solution and blank electrolyte, has a high charge / discharge rate at 3mV S -1 CV graph at scan rate. The redox peaks in the figure correspond to the transitions between S8, Li2S6 and Li2S, and Example 1 exhibits a higher response current, indicating a faster catalytic conversion of polysulfides.

[0066] The above is only a preferred embodiment of the present invention. The present invention can have other forms of embodiments according to the above preparation method, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst, characterized in that: The following steps are included Step 1, adding CNT to deionized water, stirring evenly to obtain a solution, taking cobalt salt, zinc salt and urea and adding them to the solution, hydrothermally synthesizing, washing, centrifuging and drying to obtain CNT-ZnCo powder; Step 2: calcining CNT-ZnCo powder at high temperature in a mixed atmosphere to obtain a CNT-ZnO / Co catalyst; Step 3: After mixing the obtained CNT-ZnO / Co catalyst and elemental sulfur, grind them evenly and transfer them to a reaction kettle, heat and keep them warm, and cool them to room temperature to obtain a lithium-sulfur battery composite positive electrode material.

2. The method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst according to claim 1, characterized in that: In the step 1, the amount of CNT used is 60-120 mg, the amount of cobalt salt is 1 mmol, and the amount of zinc salt is 0.2-4 mmol.

3. The method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst according to claim 2, characterized in that: In the step 1, the temperature of the hydrothermal synthesis is 90° C. to 120° C., and the insulation time is 8 to 12 hours; the drying temperature is 40 to 60° C., and the drying time is 10 to 12 hours.

4. A method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst according to any one of claims 1 to 3, characterized in that: In the step 3, the mass ratio of CNT-ZnO / Co to elemental sulfur is 4:4-8.

5. The method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst according to claim 4, characterized in that: In the step 2, the high temperature calcination temperature is 400-700° C. and the time is 2-6 h.

6. The method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst according to claim 5, characterized in that: In the step 3, the heating temperature is 150-160° C. and the insulation time is 10-12 h.

7. The method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst according to claim 6, characterized in that: In the step 2, the calcination atmosphere is a mixed atmosphere of argon and hydrogen or a mixed atmosphere of argon and ammonia.

8. The method for preparing a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst according to claim 7, characterized in that: The cobalt salt and zinc salt are nitrates or chlorides.

9. A lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst obtained according to the preparation method of claim 1.

10. The use of a lithium-sulfur battery positive electrode material containing a CNT-ZnO / Co catalyst in a lithium-sulfur battery according to claim 9, characterized in that: The battery is manufactured by assembling at least a positive electrode sheet, an electrolyte, a separator, and a negative electrode metal lithium sheet in sequence, and the positive electrode sheet is manufactured from a positive electrode material containing a CNT-ZnCo catalyst.